Evaluación de la eficiencia de tres insecticidas biológicos comerciales en el control del perforador del fruto (Neoleucinodes elegantalis G.) en el cultivo de naranjilla (Solanum quitoense L) - Gómez Flores, Miller Manaces (2015)
In the present research the efficiency of three commercial biological insecticide (Beauveria bassiana, Metarhizium anisopliae and Bacillus thuringienses) in the control of bollworm (Neoleucinodes elegantalis) in the cultivation of naranjilla (Solanum quitoense) was evaluated Area Selva Alegre province of Imbabura, in order to assess the degree of effectiveness of three biological insecticides alone and combined together in controlling fruitworm naranjilla cultivation; identify the best agronomic crop yield the application of different insecticides and perform economic analysis of treatments. Design Randomized Complete Blocks (RCBD) with eight treatments and three replications blocks. The total area of the experiment was 3.608 m2, the plot experience of 96 m2, useful area 32 m2, the distance between roads and blocks 2 m. Percentage of infected fruits, number of larvae per kilogram of fruit, effectiveness of insecticides, number of flowers per plant, number of commercial fruit set, fruit weight in grams, yield per plot in pounds: The variables were evaluated. Economic analysis was performed based on the yield (kg / ha) and the cost of each treatment. All variables were subjected to analysis of variance and the Tukey test at 5% was used to determine statistical difference between the means of the factors and interpretation..........